Can Computerized Cognitive Training Improve Cognition in Patients With Heart Failure?: A Review. Issue 2 (March 2019) - Kua, Zhong Jie; Valenzuela, Michael; Dong, YanHong
Abstract : Background: Cognitive impairment is highly prevalent in patients with heart failure (HF), negatively impacting self-care and consequently increasing mortality. Although computerized cognitive training (CCT) has been found to be efficacious in improving cognition in older adults, little is known about the efficacy of CCT in patients with HF. Purpose: This brief systematic review examined the feasibility and efficacy of CCT on cognitive functioning in patients with HF. Methods: PubMed, Embase, and PsychINFO electronic databases were searched to identify randomized controlled trials (RCTs) of CCT in patients with HF published from January 1, 2000, to December 31, 2017. A narrative synthesis of intervention effectiveness on individual cognitive domains and functional outcomes was provided. Risk of bias of the studies was also rated. Results: The search yielded 4 RCTs describing 3 cognitive training interventions (n = 138). Preliminary evidence indicated that CCT may enhance the processing speed and working memory of patients with HF. Intervention effects also seemed to confer transferrable benefits to functional outcomes of daily living. The outcomes of the assembled studies were assessed using the Grades of Recommendation, Assessment, Development and Evaluation system, and the quality of the evidence was found to be of moderate to low quality. Conclusion: Computerized cognitive trainings show promise in enhancing the cognition of patients with HF. The stability of the current findings would need to be tested in RCTs with larger sample sizes to validate the use of CCTs in targeting cognitive impairment and self-care abilities for patients with HF.